Potassium-selective microelectrode revealed difference in threshold potassium concentration for cortical spreading depression in female and male rat brain - Adámek, Svatopluk; Vyskočil, František (Brain research, 2011)
It has been found with potassium-selective microelectrodes that the threshold extracellular concentration of potassium [K(+)](e) for eliciting fast spreading depression from the site of administration 1.5mm away is 80% lower in the rat female cortex (8.0 ± 0.6 mM) than in the male cortex (14.4 ± 0.4mM). The rate of the first slow phase of [K(+)](e) rise before reaching the threshold and speed of SD propagation were similar for both sexes as well as the rise of the second active fast phase of the [K(+)](e) increase. Lower [K(+)](e) threshold in females can facilitate the rapid K(+) release from the nerve tissue cells that may cause a cerebrovascular vasodilatation and the attack of migraine pain.
Keywords: Cortical Spreading Depression; zvířata; Rats; Sex Characteristics; draslík; Cerebral Cortex; Brain Chemistry; elektrofyziologie; Potassium; mužské pohlaví; mozek - chemie; mikroelektrody; mozková kůra; krysa rodu Rattus; ženské pohlaví; Electrophysiology; Animals; šířící se kortikální deprese; Microelectrodes; Male; pohlavní dimorfismus; Female